Effects of alkalinity, extremely low carbon dioxide concentration and irradiance on spectral properties, phycobilisome, photosynthesis, photosystems and functional groups of the native cyanobacterium Calothrix sp. ISC 65 - Abbasi, B.; Shokravi, Sh.; Golsefidi, M.Ah.; Sateiee, A.; Kiaei, E. (Альгология, 2019)
In this research, Calothrix sp. ISC 65 was characterized physiologically by the combination of extremely low irradiance (2 μE·m⁻²·s⁻¹), different alkalinity (pH 7, 9, 11), and extremely limited carbon dioxide concentration (no aeration, no carbon dioxide enrichment). In this research, Calothrix sp. ISC 65 was characterized physiologically by the combination of extremely low irradiance (2 μE·m⁻²·s⁻¹), different alkalinity (pH 7, 9, 11), and extremely limited carbon dioxide concentration (no aeration, no carbon dioxide enrichment).